2021
DOI: 10.1016/j.conctc.2021.100830
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-human study of BLZ-100 (tozuleristide) demonstrates tolerability and safety in skin cancer patients

Abstract: BLZ-100 (tozuleristide) is an intraoperative fluorescent imaging agent that selectively detects malignant tissue and can be used in real time to guide tumor resection. The purpose of this study was to assess the safety, tolerability, and pharmacokinetics of BLZ-100 and to explore the pharmacodynamics of fluorescence imaging of skin tumors. In this first-in-human study, BLZ-100 was administered intravenously to 21 adult patients 2 days before excising known or suspected skin cancers. Doses were 1, 3, 6, 12, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…A preclinical test also validated the utility of BLZ-100 in providing contrast for imaging canine adenocarcinomas, squamous cell carcinomas, and mast cell tumors (52). The CTX is attractive as a targeted imaging agent for cancer because of these unique properties (56). BLZ-100 is undergoing human clinical trials and has shown negligible toxicity in humans in all clinical trials conducted to date (56,57).…”
Section: Blz-100; Tumor Paint®; Tozuleristidementioning
confidence: 89%
“…A preclinical test also validated the utility of BLZ-100 in providing contrast for imaging canine adenocarcinomas, squamous cell carcinomas, and mast cell tumors (52). The CTX is attractive as a targeted imaging agent for cancer because of these unique properties (56). BLZ-100 is undergoing human clinical trials and has shown negligible toxicity in humans in all clinical trials conducted to date (56,57).…”
Section: Blz-100; Tumor Paint®; Tozuleristidementioning
confidence: 89%
“…Several peptides have demonstrated BBB shuttling properties including GL1, SGV, PepTGN, PepC7, and angiopep-2, among others . However, CTX remains currently the only FDA-approved ligand for use in glioma surgeries and has recently shown promise in directing immunotherapies to orthotopic intracranial xenografts of GBM. , …”
Section: Discussionmentioning
confidence: 99%
“…Three of these novel probes (BLZ 100, LUM 015, and SGM-101) have reached phase III clinical trials and are expected to be approved by the FDA in a couple of years [ 95 , 96 ]. BLZ 100, used for real-time tumor detection during brain and breast cancer surgeries, consists of a natural chlorotoxin peptide, which targets the protein components of cholesterol-rich lipid rafts from cancer lesions [ 97 ]. LUM 015 contains a Cy5 fluorophore linked to a cathepsin activatable peptide, being used in combination with the LUM imaging system for fluorescent-guided surgery in residual breast cancer, gastrointestinal cancer, and prostate cancer [ 98 ].…”
Section: Pafolacianine In Comparison With Other Similar Agents Used F...mentioning
confidence: 99%